EXPLORING THE IMPACT OF COMMUNITY-BASED EDUCATION ON TEAMWORK SKILLS AMONG NURSING PROFESSIONAL STUDENTS DURING COMMUNITY AND WETLAND HEALTH PLACEMENTS - Yulia Yunara; Agianto Agianto; Bernadetta Germia Aridamayanti; Pannipa Chairat (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2025)
Introduction: As the demand for nursing professionals increases in response to evolving community health needs, the importance of effective educational strategies becomes more critical. Community-Based Education (CBE) offers a hands-on, context-driven approach that prepares nursing students to address real-world public health challenges. This study aimed to explore the impact of CBE on the development of teamwork skills among nursing professional students during their community and wetland health placement.Methods: A mixed-methods design was employed, combining quantitative and qualitative data collection. The quantitative component involved 31 nursing professional students who completed the Nursing Teamwork Survey (NTS). For the qualitative phase, in-depth interviews were conducted with five students until data saturation was reached. Descriptive statistics were used to analyze the quantitative data, while thematic analysis was used for the qualitative findings. Triangulation was applied to integrate both data sets. The study was conducted at Puskesmas Martapura Barat.Results: The highest mean score in the NTS domains was found in